Introduction to the Special Issue: Advancements in Interventions and Supports for People with Autism, Intellectual, and Developmental Disabilities to Improve Access to Inclusive community-Based Settings - Randall, Kayla; Gregori, Emily; Neely, Leslie (Journal of developmental and physical disabilities, 2024)
The goal of this special issue is to highlight recent work advancing supportive interventions that facilitate meaningful access for persons with autism, intellectual and developmental disabilities to inclusive community-based settings. The special issue includes a literature synthesis focused on informal education settings, interventions for critical skills such as pool side safety, and articles focused on adults with disabilities. Notable strengths include long-term follow-up of intervention effects, investigation of novel settings such as airports and informal educational settings, and inclusion of adults with disabilities.